THE EFFECT OF FERMANTATION OF BANANA KEPOK MUSA SP) FLOUR WITH YEAST TEMPE IN RATIONS ON CUT WEIGTH, CARCASS WEIGTH AND PERCENTAGE OF CARCASS OF LOCAL AGED MALE 11 WEEK - Siregar, Magdalena; Zega, Ledius (Jurnal Visi Eksakta, 2025)
This study aims to determine the effect of fermented kepok banana peel flour (Musa sp) with tempe yeast in the ration on slaughter weight, carcass weight and carcass percentage of local male ducks aged 11 weeks. This research was conducted in the experimental field of the Faculty of Animal Husbandry, HKBP Nommensen University in Simalingkar A Village, Medan Tuntungan District for 11 weeks. This study used 100 male local ducks. The research method used is an experimental method using a completely randomized design (CRD), consisting of 4 treatments and 5 replications, namely P0 (0% fermented kepok banana peel flour), P1 (5% fermented kepok banana peel flour), P2 (10% fermented kepok banana peel flour) and P3 (15% fermented kepok banana peel flour). The data obtained in this study were analyzed for variance (ANOVA) and then continued with the Honest Significant Difference (BNJ) test. The conclusion obtained from the results of the study showed that the provision of fermented kepok banana peel flour in the ration of male local ducks aged 11 weeks had a very significant effect (P<0.01) on slaughter weight and carcass weight, while the percentage of male local duck carcasses showed no significant difference. (P>0.05). Fermented kepok banana peel flour can be used a maximum of 10% in the ration of male local ducks.